Liver fibrosis is driven by protease‐activated receptor‐1 expressed by hepatic stellate cells in experimental chronic liver injury. Issue 5 (25th June 2020) - Poole, Lauren G.; Pant, Asmita; Cline‐Fedewa, Holly M.; Williams, Kurt J.; Copple, Bryan L.; Palumbo, Joseph S.; Luyendyk, James P.
Abstract: Background: Blood coagulation protease activity is proposed to drive hepatic fibrosis through activation of protease‐activated receptors (PARs). Whole‐body PAR‐1 deficiency reduces experimental hepatic fibrosis, and in vitro studies suggest a potential contribution by PAR‐1 expressed by hepatic stellate cells. However, owing to a lack of specific tools, the cell‐specific role of PAR‐1 in experimental hepatic fibrosis has never been formally investigated. Using a novel mouse expressing a conditional PAR‐1 allele, we tested the hypothesis that PAR‐1 expressed by hepatic stellate cells contributes to hepatic fibrosis. Methods: PAR‐1 flox/flox mice were crossed with mice expressing Cre recombinase controlled by the lecithin retinol acyltransferase (LRAT) promoter, which induces recombination in hepatic stellate cells. Male PAR‐1 flox/flox /LRATCre and PAR‐1 flox/flox mice were challenged twice weekly with carbon tetrachloride (CCl4, 1 mL/kg i.p.) for 6 weeks to induce liver fibrosis. Results: PAR‐1 mRNA levels were reduced (>95%) in hepatic stellate cells isolated from PAR‐1 flox/flox /LRATCre mice. Hepatic stellate cell activation was evident in CCl4 ‐challenged PAR‐1 flox/flox mice, indicated by increased α‐smooth muscle actin labeling and induction of several profibrogenic genes. CCl4 ‐challenged PAR‐1 flox/flox mice displayed robust hepatic collagen deposition, indicated by picrosirius red staining and type I collagen immunolabeling. Notably, stellate cell activation and collagen deposition were significantly reduced (>30%) in PAR‐1 flox/flox /LRATCre mice. Importantly, the reduction in liver fibrosis was not a consequence of reduced acute CCl4 hepatotoxicity in PAR‐1 flox/flox /LRATCre mice. Conclusions: The results constitute the first direct experimental evidence that PAR‐1 expressed by stellate cells directly promotes their profibrogenic phenotype and hepatic fibrosis in vivo .